Analysis of the Factors that Affect to Visited Interest to the Kolam Pancing and Warung Lesehan “CSDW” in the Kalipecabean Village, Candi Subdistrict, Sidoarjo Regency, East Java - Dwin Yolandari Makhfiroh (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Kolam Pancing dan Warung Lesehan "CSDW" is one of the fishing pond located in the Sidoarjo regency. This study was conducted to analyze the behavior of visitors Kolam Pancing dan Warung Lesehan "CSDW", factors that affect the interests and factors which have been the dominant influence. This research method using descriptive study and the type of data used are primary data and secondary data. Determination of the number of samples using the formula of linear time function and the sampling technique using nonprobability sampling. The method of collecting data by interviews, observations, questionnaires and documentation. The variables used in this study for the independent variable is the individual factors, environmental factors, psychological factors and the marketing mix, while the dependent variable is the interest to visit. Methods of data analysis using classical assumption test, multiple linear regression analysis and statistical tests. The results showed that the independent variables used have a significant impact together on the dependent variable and generate a regression model Y= 2,968 – 0,067X1 + 0,136 X2 + 0,211 X3 + 0,102 X4 + e. While partially, the independent variables that affect significantly ie environmental factors, psychological factors and the marketing mix. Keywords: visiting interest, kolam pancing and warung lesehan “CSDW”